Efficacy and safety of selective pan-fibroblast growth factor receptor (FGFR) tyrosine kinase inhibitors in FGFR-altered urothelial carcinoma - Yuxuan Song; Yiqing Du; Shan Jiang; Yun Peng; Xing Luo; Tao Xu (Pharmacological Research)
Fibroblast growth factor receptor (FGFR) alteration is one of the common driver alterations in urothelial carcinoma (UC). FGFR alterations contribute to anti-tumor immunity inhibition and are associated with attenuated response to immune checkpoint inhibitor (ICI) or chemotherapy. Selective pan-FGFR tyrosine kinase inhibitor (FGFRi) has been approved for FGFR-altered UC. However, the comparative efficacy and safety of FGFRi with ICI or chemotherapy remains under debate. We analyzed 865 UC patients including 447 with FGFRi and 418 with ICI or chemotherapy. FGFRi showed better recurrence-free survival for non-muscle invasive UC and higher objective response for advanced UC than ICI or chemotherapy. However, FGFRi demonstrated no benefit for the survival of advanced UC and led to more treatment-related adverse events, especially adverse events causing dose interruptions. It is worth noting that patients with liver metastasis might benefit from FGFRi in terms of both prognosis and response. In summary, FGFRi offered higher efficacy and lower safety in second-line treatment of FGFR-altered UC. It is crucial for clinicians to balance the efficacy and safety in different tumor stages when considering the use of FGFRi for UC treatment.